Biosynthesis of palladium nanoparticles using Poplar leaf extract and its application in Suzuki coupling reaction. Issue 3 (22nd September 2016) - Liu, Guanghui; Bai, Xuefeng
Abstract : A green route for the synthesis of palladium (Pd) nanoparticles (Pd NPs) employing Poplar leaf extract as a reducing and capping agent is described. The as‐prepared Pd NPs are spherical with a face centred cubic structure, a particle distribution of 2.2–6.8 nm and an average particle size of 4.2 nm. The application of this catalyst toward homogeneous Suzuki coupling reactions was investigated. The Pd NPs afforded a yield of 98.86% in the Suzuki coupling reaction of 4‐bromotoluene with phenylboronic acid using 0.01 mmol% of the catalyst at 60°C for 30 min under an air atmosphere.